LC-MS/MS metabolomics analysis: Leaf harvesting plus pesticide spraying can further improve the growth quality of Kandelia obovata Sheue & al. - Zhao, Ziyu; Yang, Sheng; Chen, Qiuxia (Frontiers in Plant Science, 2025)
This study aims to reveal the changes in the growth of new leaves and soil nutrient capacity of Kandelia candel under different pest control treatments, and to explore the effects of each treatment on the metabolome of new leaves and soil of Kandelia candel by non-targeted metabolomics. Four treatments were set up in Yanpu Bay, Wenzhou, Zhejiang from June to October 2023: CK (T1), Leaf picking (T2), Spraying (T3), Leaf picking plus Spraying (T4). The experimental results showed that all three treatments promoted the germination of new branches, the increase in the number of leaves and the improvement of plant quality to varying degrees, among which T4 had the most significant effect. LC-MS/MS analysis showed that the metabolites of soil and new leaves changed significantly under the four treatment conditions, mainly involving the formation of lipids and lipid molecules, organic acids and their derivatives in the soil, and lipids and lipid molecules, phenylpropanoids and polyketides in the new leaves. 528 metabolites in the soil and 1174 metabolites in the new leaves were identified. This study revealed the differences in metabolites of soil and new leaves under different pest control treatments by combining Spearman analysis and KEGG database. The results showed that primary and secondary metabolites in the soil, such as lipids, lipid-like molecules, and organic acids and their derivatives, may play an important role in pest resistance, especially the biosynthesis of the linoleic acid pathway and secondary bile acid biosynthesis, which had the highest enrichment. Similarly, primary and secondary metabolites in new leaves, such as lipids, lipid-like molecules, phenylpropanoids, and polyketides, may also play an important role in pest resistance, with the highest biosynthesis enrichment of flavonoid and flavonol biosynthesis and flavonoid biosynthesis. These findings provide a new theoretical basis for the metabolic mechanism of pest control in Kandelia candel, and provide new ideas and useful metabolites for genetic improvement of mangrove plant resistance using molecular breeding technology.